Unlocking the promise of UK health data: considering the case for a charitable GP data trust - Redhead, Caroline A B; Bowden, Catherine; Ainsworth, John; Burns, Nigel; Cunningham, James; Holm, Søren; Devaney, Sarah (Medical law review, 2025)
The UK National Health Service general practice (GP) patient data constitute a rich research resource, but collecting, managing, and sharing patient data present challenges. In May 2021, to address these challenges, substantial changes to the system for processing pseudonymized GP patient data in England were announced. As part of an opt-out process, patient consent to sharing GP data was deemed to have been given. However, when over a million people quickly acted to opt out of the new system, the process was paused, and an engagement exercise commenced, whose aim was to inform a re-designed programme addressing patient concerns. In this article, we present and discuss the findings of the General Practice Data Trust pilot study, which has investigated people's reasons for opting out of sharing their data, and, looking for practical solutions to their concerns, has discussed with participants the concept of a 'data trust' to manage the sharing of patient data. Making a conceptual argument for the use of the (relatively new) charitable incorporated organization as a governance model for a GP data trust, we demonstrate how this could address patients' concerns and represent a more attractive means of stewarding GP data for research and service planning purposes.